Biochar-loaded nano-iron as well as preparation method and application thereof

By loading nano-iron on modified biochar, the problem of nano-iron prone to agglomeration and instability in soil heavy metal pollution repair is solved, and the efficient heavy metal removal effect is achieved, which is suitable for a wide range of soil heavy metal pollution repair applications.

CN119608107APending Publication Date: 2025-03-14JIANGSU UNIV

Patent Information

Application Number
CN202411186571.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-28
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The application of nano zero-valent iron in the field of soil heavy metal pollution repair is limited by the problems of its prone to agglomeration, instability and the occupation of active sites, resulting in a low removal rate of heavy metals.

Method used

By loading nanoferrous on biochar, the pore structure and large specific surface area of ​​biochar are used to improve the stability and distribution of nanoferrous, and biochar is not easy to agglomerate and has good stability. The specific method includes modifying, charring, and activating the biomass, loading the iron ions in a solution containing trivalent iron ions, and reducing the iron ions through a plant aqueous extract.

Benefits of technology

It has achieved biochar-loaded nano-iron not easy to agglomerate, good stability, and high heavy metal removal rate. The heavy metal removal rate can reach 73.1% in 15 days, which is suitable for soil heavy metal pollution repair.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005013683900000061
    Figure BDA0005013683900000061
  • Figure BDA0005013683900000071
    Figure BDA0005013683900000071
  • Figure BDA0005013683900000081
    Figure BDA0005013683900000081
Patent Text Reader

Abstract

The invention relates to the technical field of soil heavy metal pollution remediation, and discloses biochar loaded nano-iron as well as a preparation method and application thereof. The invention relates to a preparation method of biochar-loaded nano-iron, which comprises the following steps: by taking biomass as a raw material, modifying, carbonizing and activating to obtain modified biochar, then putting the modified biochar into a solution containing ferric ions to load iron ions to obtain biochar loaded with the iron ions, and drying the biochar loaded with the iron ions to obtain the biochar loaded with the nano-iron. And finally, reducing the iron ions in the biochar loaded with the iron ions by using a plant water extract to obtain the biochar loaded nano-iron. The biochar-loaded nano-iron provided by the invention is not easy to agglomerate, good in stability and high in heavy metal removal rate, the heavy metal removal rate can reach 73.1% within 15 days, and the biochar-loaded nano-iron can be widely applied to remediation of heavy metal pollution of soil.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of soil heavy metal pollution remediation, and in particular to biochar-loaded nano-iron and a preparation method and application thereof. Background Art

[0002] With the rapid economic development and the continuous advancement of urbanization, the waste generated by human activities has inevitably caused pollution to the soil environment; among them, heavy metal pollution is particularly prominent, posing a major threat to the ecological environment and human health; therefore, finding effective soil heavy metal pollution remediation technology has become the research focus of many scientific researchers.

[0003] At present, the technologies for remediation of soil heavy metal pollution mainly include biological remediation, chemical remediation, physical remediation and nanomaterial remediation. Among them, nanomaterial remediation has the characteristics of high specific surface area and high surface reactivity, and has shown significant potential and advantages in the remediation of soil heavy metal pollution, and has therefore received widespread attention from researchers.

[0004] Nano-zero-valent iron (nZVI) is an emerging material for soil heavy metal remediation. It has the characteristics of high specific surface area, strong chemical activity, excellent reducibility and adsorption for many heavy metal ions. However, nano-zero-valent iron is easy to agglomerate, unstable and easily passivated, which seriously limits the application of nano-zero-valent iron in the field of soil heavy metal pollution remediation.

[0005] In order to overcome these shortcomings, some researchers loaded nZVI on stable carriers, such as biochar (BC), using the well-developed pore structure and large specific surface area of ​​biochar to improve the agglomeration and instability of nZVI. However, biochar itself has certain defects, such as the uneven pore structure and insufficient specific surface area, which will lead to the agglomeration of nZVI or the occupation of the active sites of nZVI, which is not conducive to the soil heavy metal remediation of nZVI.

[0006] Based on this, providing a biochar loaded with nano zero-valent iron that is not easy to agglomerate, has good stability, and has a high heavy metal removal rate has become a technical problem that needs to be urgently solved by technicians in this field. Summary of the invention

[0007] The purpose of the present invention is to provide a biochar-loaded nano-iron and a preparation method and application thereof. The biochar-loaded nano-iron is not easy to agglomerate, has good stability and a high heavy metal removal rate.

[0008] To achieve the above object, the present invention provides the following technical solutions:

[0009] One of the technical solutions of the present invention:

[0010] A method for preparing biochar-loaded nano-iron comprises the following steps:

[0011] Biomass is used as raw material, and modified, carbonized and activated are performed to obtain modified biochar. The modified biochar is then placed in a solution containing trivalent iron ions to load iron ions to obtain biochar loaded with iron ions. Finally, plant water extract is used to reduce the iron ions in the biochar loaded with iron ions to obtain the biochar loaded with nano-iron.

[0012] Furthermore, the biomass is crop straw, wood or wood processing waste.

[0013] Furthermore, before modifying the biomass, the biomass needs to be washed with deionized water to remove surface impurities, then dried at 80-120° C. to a water content of less than 15%, crushed, and passed through a 60-mesh sieve.

[0014] Furthermore, the modification is as follows: placing the biomass in a H3PO4 solution with a volume fraction of 55%, and immersing and modifying it at room temperature for 0.5 to 1.5 hours.

[0015] Furthermore, the mass volume ratio of the biomass to the H3PO4 solution with a volume fraction of 55% is 1 g: 10 mL.

[0016] Furthermore, the carbonization is carried out under a nitrogen atmosphere with the temperature controlled at 400-600° C. and the pressure at 300-500 kPa for 1-2 hours.

[0017] Furthermore, the activation is: in an atmosphere of 25% CO2+75% N2, the temperature is controlled at 50-80°C and the activation is carried out for 2-3 hours.

[0018] Furthermore, the solution containing trivalent iron ions has a concentration of 1.2 mol·L -1 of FeCl3 solution.

[0019] Furthermore, the mass volume ratio of the modified biochar to the solution containing trivalent iron ions is 1 g:20 mL.

[0020] Furthermore, the loading is: immersion adsorption in a solution environment with a pH of 3 to 4 for 0.5 to 1 hour.

[0021] Furthermore, the plant water extract is a water extract of Spartina alterniflora.

[0022] Furthermore, the method for preparing the water extract of Spartina alterniflora comprises the following steps:

[0023] 1) washing the Spartina alterniflora with deionized water to remove surface impurities, then drying at 40-60° C. to a water content of less than 25%, crushing, and passing through a 40-mesh sieve to obtain Spartina alterniflora powder;

[0024] 2) Take 10-20 g of the Spartina alterniflora powder obtained in step 1), add 100 mL of distilled water, and extract at 80-100° C. for 1-2 h to obtain the Spartina alterniflora water extract.

[0025] Furthermore, the mass volume ratio of the biochar loaded with iron ions to the water extract of Spartina alterniflora is 1 g:5 mL.

[0026] Furthermore, the reduction comprises: controlling the stirring speed to 30 r / min and reacting for 10 to 20 min.

[0027] The second technical solution of the present invention:

[0028] The biochar-loaded nano-iron is prepared by the above-mentioned method for preparing biochar-loaded nano-iron.

[0029] The third technical solution of the present invention:

[0030] The above-mentioned application of biochar loaded with nano-iron in the remediation of soil heavy metal pollution.

[0031] Compared with the prior art, the present invention has the following beneficial effects:

[0032] The biochar-loaded nano-iron provided by the present invention is not easy to agglomerate, has good stability, and has a high heavy metal removal rate. The heavy metal removal rate can reach 73.1% in 15 days, and can be widely used in soil heavy metal pollution remediation;

[0033] The preparation method of biochar-loaded nano-iron provided by the invention has readily available raw materials, a simple preparation method, little pollution to the environment, and high economic value. DETAILED DESCRIPTION

[0034] Now, various exemplary embodiments of the present invention are described in detail, and this detailed description should not be considered as a limitation of the present invention, but should be understood as a more detailed description of certain aspects, characteristics and embodiments of the present invention. It should be understood that the terms described in the present invention are only for describing specific embodiments and are not used to limit the present invention.

[0035] In addition, for the numerical range in the present invention, it is understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0036] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0037] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.

[0038] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0039] In the following examples and comparative examples, the room temperature is 25±2°C.

[0040] In the following examples and comparative examples, the biomass raw materials and drugs used were commercially available.

[0041] In the following embodiment, a method for preparing biochar-loaded nano-iron comprises the following steps:

[0042] 1) washing the biomass with deionized water to remove surface impurities, then drying at 80-120° C. to a moisture content of less than 15%, crushing, and passing through a 60-mesh sieve to obtain biomass powder;

[0043] Among them, biomass is crop straw, wood or wood processing waste;

[0044] 2) placing the biomass powder obtained in step 1) in a 55% H3PO4 solution with a mass volume ratio of 1 g to 55% H3PO4 solution, immersing and modifying the biomass powder at room temperature for 0.5 to 1.5 h, filtering the biomass powder, and drying the biomass powder at 80 to 120° C. for 2 h to obtain modified biomass;

[0045] 3) placing the modified biomass obtained in step 2) in a tubular furnace, controlling the temperature to 400-600° C. and the pressure to 300-500 kPa under a nitrogen atmosphere, and carbonizing for 1-2 hours to obtain biochar;

[0046] 4) Activating the biochar obtained in step 3) for 2 to 3 hours under a 25% CO2 + 75% N2 atmosphere at a controlled temperature of 50 to 80°C to obtain modified biochar;

[0047] 5) According to the mass volume ratio of modified biochar to FeCl3 solution of 1g:20mL, the modified biochar obtained in step 4) was placed in a solution with a concentration of 1.2mol·L -1 The solid-liquid mixture is added to a FeCl3 solution, and the pH value is adjusted to 3-4 by using hydrochloric acid, and then immersed and adsorbed for 0.5-1h to obtain biochar loaded with iron ions;

[0048] 6) washing the Spartina alterniflora with deionized water to remove surface impurities, then drying at 40-60° C. to a water content of less than 25%, crushing, and passing through a 40-mesh sieve to obtain Spartina alterniflora powder;

[0049] 7) taking 10-20 g of the Spartina alterniflora powder obtained in step 6), adding 100 mL of distilled water, and extracting at 80-100° C. for 1-2 h to obtain an Spartina alterniflora aqueous extract;

[0050] 8) According to the mass volume ratio of the biochar loaded with iron ions to the water extract of Spartina alterniflora of 1 g: 5 mL, the biochar loaded with iron ions obtained in step 5) was added to the water extract of Spartina alterniflora, the stirring speed was controlled to 30 r / min, the reaction was carried out for 10 to 20 min, and then the reaction was carried out by filtering and drying at 50 to 60° C. for 30 min to obtain the biochar loaded with nano-iron.

[0051] Example 1

[0052] A biochar loaded with nano-iron

[0053] 1) Wash the rice straw with deionized water to remove surface impurities, then dry it at 100° C. to a moisture content of 15%, grind it, and pass it through a 60-mesh sieve to obtain biomass powder;

[0054] 2) placing the biomass powder obtained in step 1) in a 55% H3PO4 solution with a mass volume ratio of 1 g to 55% H3PO4 solution, immersing and modifying the biomass powder at room temperature for 0.5 h, filtering the biomass powder, and drying the biomass powder at 100° C. for 2 h to obtain modified biomass;

[0055] 3) placing the modified biomass obtained in step 2) in a tubular furnace, controlling the temperature to 400° C. and the pressure to 300 kPa under a nitrogen atmosphere, and carbonizing for 1.5 h to obtain biochar;

[0056] 4) Activating the biochar obtained in step 3) for 2.5 h in an atmosphere of 25% CO2 + 75% N2 at a temperature of 50°C to obtain modified biochar;

[0057] 5) According to the mass volume ratio of modified biochar to FeCl3 solution of 1g:20mL, the modified biochar obtained in step 4) was placed in a solution with a concentration of 1.2mol·L -1 The solid-liquid mixture was added to a FeCl3 solution, and the pH value was adjusted to 3-4 using hydrochloric acid, and then immersed and adsorbed for 1 hour to obtain biochar loaded with iron ions;

[0058] 6) washing the Spartina alterniflora with deionized water to remove surface impurities, then drying at 50° C. to a water content of 25%, crushing, and passing through a 40-mesh sieve to obtain Spartina alterniflora powder;

[0059] 7) taking 15 g of the Spartina alterniflora powder obtained in step 6), adding 100 mL of distilled water, and extracting at 90° C. for 1.5 h to obtain an Spartina alterniflora aqueous extract;

[0060] 8) According to the mass volume ratio of biochar loaded with iron ions to the water extract of Spartina alterniflora of 1 g: 5 mL, the biochar loaded with iron ions obtained in step 5) was added to the water extract of Spartina alterniflora, the stirring speed was controlled to 30 r / min, the reaction was carried out for 15 min, and then the mixture was filtered and dried at 55° C. for 30 min to obtain the biochar loaded with nano-iron.

[0061] Comparative Example 1

[0062] A biochar loaded with nano-iron

[0063] The same as Example 1, except that in step 2), a H3PO4 solution with a volume fraction of 40% is used to prepare the modified biomass.

[0064] Comparative Example 2

[0065] A biochar loaded with nano-iron

[0066] The same as Example 1, except that in step 2), a H3PO4 solution with a volume fraction of 70% is used to prepare the modified biomass.

[0067] The biochar loaded with nano-iron prepared in Example 1 and Comparative Examples 1-2 was tested for soil heavy metal pollution remediation performance, and the testing method was as follows:

[0068] 1) According to the heavy metal Cd content of 20 mg / kg, the soil was artificially contaminated with CdCl2 and left to stand for 30 days to obtain artificially contaminated heavy metal soil;

[0069] 2) adding biochar-loaded nano-iron to artificially contaminated heavy metal soil at a ratio of 6 kg of biochar-loaded nano-iron per cubic meter of artificially contaminated heavy metal soil, and after 15 days, detecting the Cd content in the soil and calculating the Cd removal rate;

[0070] The test results are shown in Table 1;

[0071] Table 1 Cd removal rate

[0072]

[0073] It can be seen from the data in Table 1 that the concentration of H3PO4 solution will affect the heavy metal removal rate of biochar loaded with nano-iron; the present invention uses phosphoric acid to modify biomass, and its purpose is to use the corrosiveness of phosphoric acid to destroy part of the organic structure in the biomass. Too low a phosphoric acid concentration will result in the organic structure in the organic matter cannot be destroyed, the micropore structure is small, and there is not enough space to load nano-iron, which is not conducive to the heavy metal removal rate of biochar loaded with nano-iron; while too high a phosphoric acid concentration will cause the organic structure in the biomass to be excessively destroyed, the micropore structure is too large, and it is impossible to adsorb the solution containing trivalent iron ions, which is not conducive to the heavy metal removal rate of biochar loaded with nano-iron. Experiments have shown that modifying biomass with a volume fraction of 55% H3PO4 solution can achieve the optimal heavy metal removal rate.

[0074] Embodiments 2 to 6

[0075] A biochar loaded with nano-iron

[0076] The same as Example 1, except that in step 2), the durations of the immersion modification are 0.7 h, 0.9 h, 1.1 h, 1.3 h and 1.5 h, respectively.

[0077] The biochar loaded with nano-iron prepared in Examples 2 to 6 was tested for soil heavy metal pollution remediation performance, and the testing method was as follows:

[0078] 1) According to the heavy metal Cd content of 20 mg / kg, the soil was artificially contaminated with CdCl2 and left to stand for 30 days to obtain artificially contaminated heavy metal soil;

[0079] 2) adding biochar-loaded nano-iron to artificially contaminated heavy metal soil at a ratio of 6 kg of biochar-loaded nano-iron per cubic meter of artificially contaminated heavy metal soil, and after 15 days, detecting the Cd content in the soil and calculating the Cd removal rate;

[0080] The test results are shown in Table 2;

[0081] Table 2 Cd removal rate

[0082]

[0083] It can be seen from the data in Table 2 that the immersion modification time of biomass in H3PO4 solution will affect the heavy metal removal rate of biochar loaded with nano-iron. Experiments have shown that immersion modification for 1.3h can optimally corrode the organic structure in organic matter, which is conducive to the subsequent formation of a microporous structure that is conducive to nano-iron loading, thereby achieving the optimal heavy metal removal rate.

[0084] Embodiments 7 to 10

[0085] A biochar loaded with nano-iron

[0086] Same as Example 5, except that in step 3), the carbonization temperatures are 450°C, 500°C, 550°C and 600°C respectively.

[0087] The biochar loaded with nano-iron prepared in Examples 7 to 10 was tested for soil heavy metal pollution remediation performance, and the testing method was as follows:

[0088] 1) According to the heavy metal Cd content of 20 mg / kg, the soil was artificially contaminated with CdCl2 and left to stand for 30 days to obtain artificially contaminated heavy metal soil;

[0089] 2) adding biochar-loaded nano-iron to artificially contaminated heavy metal soil at a ratio of 6 kg of biochar-loaded nano-iron per cubic meter of artificially contaminated heavy metal soil, and after 15 days, detecting the Cd content in the soil and calculating the Cd removal rate;

[0090] The test results are shown in Table 3;

[0091] Table 3 Cd removal rate

[0092]

[0093] Examples 11 to 14

[0094] A biochar loaded with nano-iron

[0095] Same as Example 7, except that in step 3), the carbonization pressures are 350 kPa, 400 kPa, 450 kPa and 500 kPa respectively.

[0096] The biochar loaded with nano-iron prepared in Examples 11 to 14 was tested for soil heavy metal pollution remediation performance, and the testing method was as follows:

[0097] 1) According to the heavy metal Cd content of 20 mg / kg, the soil was artificially contaminated with CdCl2 and left to stand for 30 days to obtain artificially contaminated heavy metal soil;

[0098] 2) adding biochar-loaded nano-iron to artificially contaminated heavy metal soil at a ratio of 6 kg of biochar-loaded nano-iron per cubic meter of artificially contaminated heavy metal soil, and after 15 days, detecting the Cd content in the soil and calculating the Cd removal rate;

[0099] The test results are shown in Table 4;

[0100] Table 4 Cd removal rate

[0101]

[0102] It can be seen from the data in Tables 3 and 4 that both the carbonization temperature and pressure will affect the heavy metal removal rate of biochar-loaded nano-iron. Experiments have shown that controlling the carbonization temperature to 450°C and the pressure to 400 kPa can form a microporous structure that is most conducive to the subsequent loading of nano-iron, improve the stability of nano-iron, and inhibit the agglomeration of nano-iron, which is beneficial to the heavy metal removal rate of biochar-loaded nano-iron.

[0103] Comparative Example 3

[0104] A biochar loaded with nano-iron

[0105] Same as Example 12, except that in step 4), the biochar is activated in an atmosphere of 10% CO2 + 90% N2.

[0106] Comparative Example 4

[0107] A biochar loaded with nano-iron

[0108] Same as Example 12, except that in step 4), the biochar is activated in an atmosphere of 40% CO2+60% N2.

[0109] The biochar loaded with nano-iron prepared in Comparative Examples 3 to 4 was tested for soil heavy metal pollution remediation performance, and the testing method was as follows:

[0110] 1) According to the heavy metal Cd content of 20 mg / kg, the soil was artificially contaminated with CdCl2 and left to stand for 30 days to obtain artificially contaminated heavy metal soil;

[0111] 2) adding biochar-loaded nano-iron to artificially contaminated heavy metal soil at a ratio of 6 kg of biochar-loaded nano-iron per cubic meter of artificially contaminated heavy metal soil, and after 15 days, detecting the Cd content in the soil and calculating the Cd removal rate;

[0112] The test results are shown in Table 5;

[0113] Table 5 Cd removal rate

[0114]

[0115] It can be seen from the data in Table 5 that when the activated carbon is activated, changing the volume ratio of carbon dioxide gas will affect the heavy metal removal rate of biochar loaded with nano-iron; the present invention utilizes carbon dioxide gas to etch the activated carbon to further improve the micropore structure in the activated carbon, which is beneficial to the subsequent loading of nano-iron. Too high or too low carbon dioxide concentration will lead to a reduction in the number of micropores or an excessively large pore size, which is not conducive to the subsequent loading of nano-iron. Experiments have shown that activation in an atmosphere of 25% CO2+75% N2 can achieve the optimal heavy metal removal rate.

[0116] Embodiments 15-16

[0117] A biochar loaded with nano-iron

[0118] Same as Example 12, except that in step 4), the activation temperatures are 75°C and 80°C respectively.

[0119] The biochar loaded with nano-iron prepared in Comparative Examples 3 to 4 was tested for soil heavy metal pollution remediation performance, and the testing method was as follows:

[0120] 1) According to the heavy metal Cd content of 20 mg / kg, the soil was artificially contaminated with CdCl2 and left to stand for 30 days to obtain artificially contaminated heavy metal soil;

[0121] 2) adding biochar-loaded nano-iron to artificially contaminated heavy metal soil at a ratio of 6 kg of biochar-loaded nano-iron per cubic meter of artificially contaminated heavy metal soil, and after 15 days, detecting the Cd content in the soil and calculating the Cd removal rate;

[0122] The test results are shown in Table 6;

[0123] Table 6 Cd removal rate

[0124]

[0125] It can be seen from the data in Table 6 that when the activated carbon is activated, the activation temperature will affect the heavy metal removal rate of biochar loaded with nano-iron. Experiments have shown that controlling the activation temperature to 75°C can form more micropores that are conducive to the formation of nano-iron, thereby improving the heavy metal removal rate of biochar loaded with nano-iron.

[0126] Comparative Example 5

[0127] A biochar loaded with nano-iron

[0128] The same as Example 15, except that in step 8), the stirring speed is 20 r / min.

[0129] Comparative Example 6

[0130] A biochar loaded with nano-iron

[0131] Same as Example 15, except that in step 8), the stirring speed is 40 r / min.

[0132] The biochar loaded with nano-iron prepared in Comparative Examples 5 to 6 was tested for soil heavy metal pollution remediation performance, and the testing method was as follows:

[0133] 1) According to the heavy metal Cd content of 20 mg / kg, the soil was artificially contaminated with CdCl2 and left to stand for 30 days to obtain artificially contaminated heavy metal soil;

[0134] 2) adding biochar-loaded nano-iron to artificially contaminated heavy metal soil at a ratio of 6 kg of biochar-loaded nano-iron per cubic meter of artificially contaminated heavy metal soil, and after 15 days, detecting the Cd content in the soil and calculating the Cd removal rate;

[0135] The test results are shown in Table 7;

[0136] Table 7 Cd removal rate

[0137]

[0138] It can be seen from the data in Table 7 that when using the water extract of Spartina alterniflora to reduce iron ions, changing the stirring speed will lead to a significant decrease in the heavy metal removal rate. The reason is that too low a stirring speed will cause the iron ions adsorbed by the activated carbon to be decomposed into the solution, and the iron ions will be reduced in the solution and cannot be effectively loaded. If the stirring speed is too high, the large centrifugal effect will cause the nano-iron to be unable to be effectively adsorbed in the microporous structure of the activated carbon, resulting in a decrease in the loading rate of the nano-iron, thereby affecting the heavy metal removal rate of the biochar loaded nano-iron.

[0139] Regional pilot

[0140] The biochar loaded nano-iron prepared in Example 15 was used for a regional pilot test in a heavy metal contaminated soil. The specific method includes the following steps:

[0141] 1) Using the chessboard sampling method, collect heavy metal contaminated soil and detect the Cd content in the heavy metal contaminated soil;

[0142] 2) applying the biochar-loaded nano-iron to the surface of the heavy metal-contaminated soil at a ratio of 5 kg of biochar-loaded nano-iron per 100 square meters of heavy metal-contaminated soil, controlling the tillage depth to 10 cm, and tilling the heavy metal-contaminated soil;

[0143] 3) On the 15th, 30th and 45th days, the heavy metal contaminated soil was collected, the Cd content in the heavy metal contaminated soil was detected, and the Cd removal rate was calculated;

[0144] The regional pilot results are shown in Table 8;

[0145] Table 8 Regional pilot

[0146]

[0147] It can be seen from the data in Table 8 that through actual regional pilot projects, the Cd removal rate of the biochar-loaded nano-iron provided by the present invention can reach 62.1% on the 15th day, 79.1% on the 30th day, and 88.2% on the 45th day. The heavy metal removal rate is high and can be widely used in soil heavy metal pollution remediation.

[0148] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that the specific implementation methods of the present invention can still be modified or replaced by equivalents. Any modification or equivalent replacement that does not depart from the spirit and scope of the present invention should be covered within the scope of protection of the claims of the present invention.

Claims

1. A method for preparing biochar-loaded nano-iron, characterized in that: The following steps are involved: Biomass is used as raw material, and modified, carbonized and activated are performed to obtain modified biochar. The modified biochar is then placed in a solution containing trivalent iron ions to load iron ions to obtain biochar loaded with iron ions. Finally, plant water extract is used to reduce the iron ions in the biochar loaded with iron ions to obtain the biochar loaded with nano-iron.

2. The method for preparing biochar-loaded nano-iron according to claim 1, characterized in that: The biomass is crop straw, wood or wood processing waste.

3. The method for preparing biochar-loaded nano-iron according to claim 1, characterized in that: The modification comprises placing the biomass in a H3PO4 solution with a volume fraction of 55%, and immersing and modifying it for 0.5 to 1.5 hours at room temperature; the carbonization comprises controlling the temperature at 400 to 600°C and the pressure at 300 to 500 kPa under a nitrogen atmosphere for carbonization for 1 to 2 hours; and the activation comprises controlling the temperature at 50 to 80°C and activating it for 2 to 3 hours under a 25% CO2 + 75% N2 atmosphere.

4. The method for preparing biochar-loaded nano-iron according to claim 1, characterized in that: The solution containing trivalent iron ions has a concentration of 1.2 mol·L -1 of FeCl3 solution.

5. The method for preparing biochar-loaded nano-iron according to claim 1, characterized in that: The loading is: immersion adsorption in a solution environment with a pH of 3 to 4 for 0.5 to 1 hour.

6. The method for preparing biochar-loaded nano-iron according to claim 1, characterized in that: The plant water extract is the Spartina alterniflora water extract.

7. The method for preparing biochar-loaded nano-iron according to claim 6, characterized in that: The preparation method of the Spartina alterniflora water extract comprises the following steps: 1) washing the Spartina alterniflora with deionized water to remove surface impurities, then drying at 40-60° C. to a water content of less than 25%, crushing, and passing through a 40-mesh sieve to obtain Spartina alterniflora powder; 2) Take 10-20 g of the Spartina alterniflora powder obtained in step 1), add 100 mL of distilled water, and extract at 80-100° C. for 1-2 h to obtain the Spartina alterniflora water extract.

8. The method for preparing biochar-loaded nano-iron according to claim 1, characterized in that: The reduction is as follows: controlling the stirring speed to 30 r / min and reacting for 10 to 20 minutes.

9. Biochar-loaded nano-iron prepared by the method for preparing biochar-loaded nano-iron as claimed in any one of claims 1 to 8.

10. Use of the biochar loaded with nano-iron as claimed in claim 9 in the remediation of soil heavy metal pollution.

Citation Information

Patent Citations

  • Magnetic active carbon adsorbent based on waste biomass and preparation method and applications thereof

    CN108671886A

  • Nanometer zero-valent iron-biochar composite material, and preparation method and application thereof

    CN108911005A

  • Catalyst for pollutant degradation under natural light and preparation method of catalyst

    CN112452320A

  • Preparation and application of poplar sawdust biochar loaded nano zero-valent iron composite material

    CN113477217A

Cited By

  • Biochar-plant combined remediation method for heavy metal contaminated soil of mine

    CN120169819A

  • Biochar material and method for adsorbing heavy metals in wormcast

    CN121060460A